Optimization of Counseling by the Binmas Unit to Prevent Narcotics Abuse in Tulang Bawang Police Jurisdiction - Panji Winata Erwin (Police Studies Review, 2021)
This research is motivated by the number of criminal acts of drug abuse in Tulang Bawang district which is still high and does not show a decrease at all. Various prevention efforts have been carried out by the Binmas Unit of the Tulang Bawang Police in suppressing drug abuse, but there are still shortcomings, therefore researchers conducted a study to determine the efforts of coaching and counseling the Binmas Unit in reducing the number of drug abuse. The approach used in this research is a qualitative approach and this type of research is descriptive analytic. The focus of the research is on optimizing the Binmas Unit in suppressing drug abuse with the jurisdiction of the Tulang Bawang Police. Sources of information from the Head of Binmas and the Binmas Unit of the Tulang Bawang Police, especially those who play a role in the field of guidance and counseling as well as the local community. Data collection techniques by interview, observation, and document review. Test the validity of the data by data triangulation. Test by providing a detailed, clear and systematic description. Analysis with data reduction. The results of the study indicate that the efforts of coaching and counseling the Binmas Unit in suppressing drug abuse by looking at the readiness, implementation and inhibiting factors of coaching and counseling on drug prevention. And the efforts that must be made are increasing the quantity and quality of the members, the mindset of the members, improving the facilities and infrastructure, the budget, and the methods that need to be improved in the delivery of material on drug abuse and collaboration with related agencies, bringing in direct examples of drug abusers to the public. the public, using WhatsApp social media in delivering messages to prevent drugs so that it is more attractive and has a wider scope.